Effect of Icariin on UDP-Glucuronosyltransferases in Mouse Liver - Xu, Shang-Fu; Jin, Tao; Lu, Yuan-Fu; Li, Li-Sheng; Liu, Jie; Shi, Jing-Shan (Planta Medica, 2014)
Icariin is a flavonol glycoside isolated from Epimedium genus and has been used in the treatment of sexual dysfunction and osteoporosis. Our laboratory has shown that icariin is beneficial in brain disorders and cardiovascular diseases. Since icariin is widely used with other herbs and drugs, to understand its potential herb-drug interactions is of importance. Recently, icariin was shown to inhibit UDP-glucuronosyltransferases, particularly the Ugt1 family enzymes in vitro, but little is known about such effects in vivo. This study investigated the effects of icariin on the expression of UDP-glucuronosyltransferases and cytochrome P450 enzymes in the livers of mice. Adult mice were treated with icariin at doses of 0, 40, 80, 160, and 320 mg/kg, p. o., for 7 days. Phenobarbital (120 mg/kg, p. o.) and rifampin (360 mg/kg, p. o.) were given twice daily for 3 days as positive controls. The livers were removed to determine UDP-glucuronosyltransferase activity and total RNA isolation. The UDP-glucuronosyltransferase activities towards 2-aminophenol were basically unaltered by the treatments. The expression of Cyp2b10 was increased 35-fold by phenobarbital, and Cyp3a11 was increased 4.5-fold by rifampin. Icariin did not affect Cyp2b10 and Cyp3a11 expression, but unexpectedly increased Cyp4a14 expression. Both phenobarbital and rifampin increased Ugt1a1, Ugt1a6, Ugt1a9, and icariin but did not show any suppressive effects on the Ugt1 family genes. Icariin at the highest dose (320 mg/kg) slightly increased Ugt2b1, Ugt2b5, and Ugt2b36. These findings indicate that icariin did not suppress UDP-glucuronosyltransferase expression, instead, it increased the mRNA of Cyp4a14 and slightly increased Ugt2b isoforms in mouse livers.
Keywords: icariiin; phenobarbital; rifampin; cytochrome P450; UDP-glucuronosyltransferase